Nuevos registros de pulgas de tlacuaches Didelphis virginiana (Kerr 1792) en Querétaro, México - Hernández-Camacho, Norma; Vergara-Pineda, Santiago; Acosta-Gutiérrez, Roxana; Jones, Robert W. (THERYA, 2014)
Introduction: The opossum Didelphis virginiana (Kerr 1792) is one of the eight species of marsupials that live in the northern region of America and is widely distributed in Mexico. There is a large literature in North America of studies on this species, including its ectoparasites. But in Mexico studies are scarce, and so we decided to investigate the opossum ectoparasite species richness in a suburban landscape in Querétaro, México. Methods: During January to May of 2010, we used 12 tomahawk traps to capture opossums. Each animal was immobilized with tiletilamina, and during recumbence we examined the opossums for ectoparasites. Fleas were collected in vials with 70% alcohol, then dehydrataded in 100% alcohol, and clarified with lactic acid for further identification. Results: We found four flea species on the trapped opossums (n = 26), 14 males, 12 females. The species were Ctenocephalides felis, Euhoplopsyllus glacialis affinnis, Polygenis martinezbaezi and Polygenis sp. Two of these species are considered as new records for this marsupial host in Mexico, although these species have been recorded previously in this species in the United States and in other marsupial species in Mexico. Discussion: These fleas are new records for the Mexican opossum parasite fauna. This study, although initially didactic, reveals relevant information about the flea species richness on opossums in fragmented habitats in a suburban landscape in Querétaro. Because fleas have potential as disease and parasite vectors, this new information may be helpful in assessing their effects on human and wildlife health. Key words: Didelphis virginiana, fleas, suburban landscape, Querétaro, México